Efeito do azospirillum brasilense e nitrogênio no teor e no rendimento de óleo nos grãos de milho, em cultivo de entressafra, visando a produção de biodiesel - Dias, Vanderlan Carneiro (Universidade Federal do Tocantins, 2017)
Biological nitrogen fixation (FBN) is presented as a viable and sustainable in the production of grasses, through the use of bacterium of the genus Azospirillum, microorganisms potential plant growth promoter. In this sense, the present work was to study the effect of using the diazotrophic bacterium Azospirillum brasilense, inoculated in seeds, in association or not with nitrogen, in the off season, the content and oil yield in corn genotypes. The tests were performed at two sowing times in a randomized complete block design (DBC) with 30 treatments and three replications. In every age, the treatments were arranged in a factorial 2x3x5, represented by two seed inoculation processes (with and without seed inoculation) Three genotypes (Orion and Al Bandeirante, open-pollinated varieties, and the Hybrid Double (AG-1051) and five doses of nitrogen N (0, 50, 100, 150 and 200 kg ha-1) held in coverage. The grain oil content were evaluated (%) and oil yield (kg ha-1). individual variance analysis was performed and subsequently pooled analysis. The use of bacterium Azospirillum brasilense, with or without nitrogen, promoted an increase in content and oil yield in grains. The variety Orion was the one that stood out when inoculated with Azospirillum bacterium, and is the most efficient when grown under low nitrogen. The adoption of this practice does not replace the use of nitrogen fertilizers, but can be an alternative to reduce producer costs.